캐주얼웨어에 나타난 그래피티 아트의 조형성 연구 -티셔츠 디자인을 중심으로 - 강병석; Byoung Suk Gaang; 임송규; Song Kyu Lim (기초조형학연구, 2015)
본 연구는 하나의 문화현상으로 인정되어 20 세기 후반에 대중문화로 자리 잡은 그래피티 아트가 패션에 도입되어 캐주얼웨어의 대표 아이템인 티셔츠 디자인에 활용되면서 자유롭고 형식에 얽매이지 않는 감성을 표현함에 있어, 그 조형적 특성이 무엇인지 파악하여 캐주얼웨어의 다양한 표현 방법을 모색하고 캐주얼웨어의 경향과 패션에 나타나는 시대적 의미를 파악하는데 목적이 있다. 연구대상은 2010 년부터 2015 년까지 컬렉션과 스트리트웨어에서 나타난 그래피티 티셔츠 1,090 개로써 그래피티 아트를 분류함에 있어 이미테이션, 소셜워드, 태깅 등 세 가지를 기준으로 하여각 항목을 내용적, 형식적 표현요소에 따라 분석하였다. 분석된 조형적 특성은 첫째, 풍자와 왜곡을 통하여 다양한 주제를 유희적으로 표현한 대상의 유희성, 둘째, 사회구성원의 다변화된 욕구에 따라 개별적이고 통속적인 메시지 전달을 특징으로 하는 의미의 개별성, 셋째, 과거 익명의 작가 필명이 현대 패션에 도입되면서 로고와 상표라는 대중적 이미지로 변화한 표현의 대중성이다. 이에 따라 현대 패션에서 표현된 그래피티 아트는 유머와 위트가 있고, 보다 세밀하고 개별적인 대중적 이미지를 원하는 현대 사회의 요구를 반영하고 있음을 알 수 있다. 패션은 이제 대중문화의 한 장르로서 다른 예술의 보조적인 수단에서 벗어나 독자적으로 흐름을 주도하고 있다. 따라서 이런 흐름에 맞춰 예술 분야를 더욱 산업화하고 패션과 텍스타일 디자인의 영역을 확대하는데 있어 본 연구가 기초자료로 활용되기를 기대한다. This study aimed to identify the periodic meanings of casual wear trend and fashion by investigating the formative features and various expression approaches of casual wear for expressing the liberal emotion unrestricted by forms as graffiti art secured its position as one of popular culture in late 20th century as being accepted as one of cultural phenomenon and was used in T-shirt design, the representative item of casual wear. 1,090 graffiti T-shirts in the collections and street wears from 2010 to 2015 were classified into three kinds, imitation, social word and tagging. Each item was analyzed by content and formative expression factor. The first formative feature was entertainment expressing a variety of themes in playful ways using satire and distortion. The second feature was the individuality of meaning characterized by expression of individual and popular message depending on diversified desires of members in a society. The third feature was the popularity of expression changed into logo and trademark as the anonymous artist name was introduced in the modern fashion. In accordance with the analysis, graffiti art expressed in the modern fashion reflected the needs of modern society requiring more delicate and individual popular image with humor and wit. As one genre of popular culture, fashion has been independently leading the fashion trend beyond the role supporting other arts. Accordingly, the results of this study will be the basic data for industrializing the field of arts more than ever as required in these days and expanding the scope of textile design.